2014
DOI: 10.3109/15622975.2014.897003
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of take-home dose privileges is associated with better-perceived sleep and with cognitive status among methadone maintenance treatment patients

Abstract: Privileges that reflect patients' abstinence and rehabilitation were also expanded to be associated with better cognitive states. These finding confirm the THD dispensing performance. Including CDT as part of the decision for dispensing THD may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Previous studies investigating sleep problems among heroin users have often used self-reported questionnaires such as the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale. 36 , 37 However, heroin users may not seek medical assistance. In order to provide another point of view, we used CPSD as the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating sleep problems among heroin users have often used self-reported questionnaires such as the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale. 36 , 37 However, heroin users may not seek medical assistance. In order to provide another point of view, we used CPSD as the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…70.2% of patients had PSQI scores >5 in a 121 heroin addicts who were receiving MMT sample [ 16 ], compared with those methadone maintenance treatment (MMT) patients who had history of longer duration of opiate usage and a shorter period in MMT with no methadone take-home doses (THD) (80.6%, PSQI > 5). MMT patients who had two weeks achievement of THD showed lower rates of poor sleep (56%, PSQI > 5) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Duration of substance abuse may have impact on quality of sleep. Peles E found that subjects with a longer duration of opiate usage had poorer sleep [ 17 ]. Pasch KE Found a longitudinal bi-directional relationships between sleep quality and addictive substance use (such as cigarettes, alcohol or marijuana) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of our participants described her practice of self-adjustment of her take-home methadone dose to allow her one full night of sleep per week. A study of the practice of allowing take-home doses by Peles et al (2014) showed that take-home doses were associated with better perception of sleep quality compared with those who did not receive take-home doses (56% vs. 80.6%, respectively). Recognizing the challenges that the COVID-19 pandemic presented regarding reducing face-to-face encounters, the U.S. Drug Enforcement Administration modified existing policy in January of 2020 to allow prescribers to prescribe Schedule II-IV controlled substances via telemedicine (Drug Enforcement Administration, 2020).…”
Section: Discussionmentioning
confidence: 99%